Cultural Representation of Transgenders in Indian Mythology (International Journal of Food and Nutritional Sciences, 2019)
Many cultures and mythologies worldwide since ages have mentioned and discussed theexistence of androgyny in addition and equivalence to the existence of male and femalegenders. Androgyny refers to the existence of both male and female characteristics as well asanatomy in the same body or person. An androgynous body is a definite kind of body thatcontains both female and male organs and hence cannot be classified as either male or femaleand is considered intersex and ambiguous.